Deciphering the interactome of Ataxin-2 and TDP-43 in iPSC-derived neurons for potential ALS targets. - Yuan Tian; Nicolette Heinsinger; Yinghui Hu; U-Ming Lim; Yi Wang; Aaron Zefrin Fernandis; Sophie Parmentier-Batteur; Becky Klein; Jason M Uslaner; Sean M Smith (PLoS ONE)
Ataxin-2 is a protein containing a polyQ extension and intermediate length of polyQ extensions increases the risk of Amyotrophic Lateral Sclerosis (ALS). Down-regulation of Ataxin-2 has been shown to mitigate TDP-43 proteinopathy in ALS models. To identify alternative therapeutic targets that can mitigate TDP-43 toxicity, we examined the interaction between Ataxin-2 and TDP-43. Co-immunoprecipitation demonstrated that Ataxin-2 and TDP-43 interact, that their interaction is mediated through the RNA recognition motif (RRM) of TDP-43, and knocking down Ataxin-2 or mutating the RRM domains rescued TDP-43 toxicity in an iPSC-derived neuronal model with TDP-43 overexpression. To decipher the Ataxin-2 and TDP-43 interactome, we used co-immunoprecipitation followed by mass spectrometry to identify proteins that interacted with Ataxin-2 and TDP-43 under conditions of endogenous or overexpressed TDP-43 in iPSC-derived neurons. Multiple interactome proteins were differentially regulated by TDP-43 overexpression and toxicity, including those involved in RNA regulation, cell survival, cytoskeleton reorganization, protein modification, and diseases. Interestingly, the RNA-binding protein (RBP), TAF15 which has been implicated in ALS was identified as a strong binder of Ataxin-2 in the condition of TDP-43 overexpression. Together, this study provides a comprehensive annotation of the Ataxin-2 and TDP-43 interactome and identifies potential therapeutic pathways and targets that could be modulated to alleviate Ataxin-2 and TDP-43 interaction-induced toxicity in ALS.